Communication skills in nursing home residents with dementia: results of a prospective intervention study over 21 months - Degen, Christina; Frankenberg, Claudia; Meyer-Kühling, Inga; Wendelstein, Britta; Knebel, Maren; Pantel, Johannes; Zenthöfer, Andreas; Rammelsberg, Peter; Andrejeva, Nadeshda; Schröder, Johannes (Zeitschrift für Gerontologie und Geriatrie, 2022)
The dementia syndrome compromises effective communication and may thus lead to social isolation, psychological distress and decreased quality of life. It is therefore of importance to maintain communication capacity in dementia as long as possible.
Online veröffentlicht am 25. Juni 2021
Gesehen am 14.12.2022